Evaluasi Pengukuran Kinerja dan Penerapan Balanced Scorecard pada PT. Citra Kridatama - Nurul Adhayanti (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
By using the Balanced Scorecard approach, the purpose of this study is to determine the level of performance and factors that affect the performance of PT CITRA KRIDATAMA. Questionnaires were distributed to 35 employees to evaluate the performance of PT CITRA KRIDATAMA. By using the Balanced Scorecard, performance measurement will be carried out from four (4) points of view: financial, consumer, internal business processes, and learning and growth. With a total score of 0.277, this study shows that there is no significant relationship between employee performance and their job. The correlation figure of 0.189 indicates that performance tends to increase and vice versa. Based on the recommended results, PT CITRA KRIDATAMA should concentrate on employee productivity. One way to create a competitive strategy in the face of the business world is to use the Balance Scorecard.